A novel photoelectrochemical sensor for bilirubin based on porous transparent TiO2 and molecularly imprinted polypyrrole. (1st January 2016) - Zhang, Chunjing; Bai, Wanbei; Yang, Zhengpeng
Abstract: Transparent photocatalytic surfaces are of ever increasing importance for the enhancement of the photocatalytic efficiency. Here, the porous transparent TiO2 (PTT) was conveniently fabricated on the glass substrate by a sol-gel process, and a novel photoelectrochemical sensing platform with excellent photochemical catalysis and molecular recognition capabilities was established for bilirubin detection based on the modification of molecularly imprinted polypyrrole (MIPPy) onto PTT surface by the molecular imprinting technique. The performance of the fabricated sensor was evaluated and the results indicated that the sensor exhibited high sensitivity in bilirubin detection, with a linear range from 0.03 to 28 μM and a limit of detection of 0.001 μM. Moreover, the sensor exhibited outstanding selectivity while used in coexisting systems containing various interferents with high concentration. The practical application of the sensor was also realized in the selective detection of bilirubin in real samples. The favorable performance of the developed bilirubin sensor can be mainly attributed to the high transparency and photoelectric activity of PTT and selective recognition and excellent conductivity of MIPPy.